A weak acid substrate with low solubility in water samples and its application
By introducing hyperbranched unsaturated polymers and double bond-containing carboxyl monomers into weak acid resins and carrying out cross-linking reactions, the problems of insufficient dissolution and carboxyl content in the water-like alkalinity test in the prior art are solved, and higher detection accuracy and efficiency are achieved.
Patent Information
- Application Number
- CN202111056407.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-09-09
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2041-09-09
AI Technical Summary
The weakly acidic resin prepared in the prior art contains unreacted polymeric monomers, which leads to dissolution in the alkalinity test of water samples, affects the accuracy, and has low carboxyl content and low efficiency.
Hyperbranched unsaturated polymers are used as substrates, and double bonds and carboxy monomers are grafted in their branches, and weak acid substrates that are lowly dissolved in water samples are prepared by cross-linking reaction after eluting the remaining monomers.
The reaction rate between weak acid substrate and alkaline substances is improved, the accuracy of alkalinity detection is enhanced, and the dissolution rate in water samples is reduced.
Smart Images

Figure BDA0003254770250000071 
Figure BDA0003254770250000081 
Figure BDA0003254770250000082
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of water quality detection, and in particular relates to a weak acid substrate with low dissolution in a water sample and an application thereof. Background Art
[0002] At present, more and more people realize that water quality is closely related to people's health and life, and is crucial to the human living environment. Water alkalinity is an important indicator for judging water quality. Therefore, how to conveniently and accurately analyze the alkalinity of various water sources is a very urgent and important demand.
[0003] There are mainly several methods for testing water alkalinity: acid-base titration, potentiometric titration, spectrophotometry, etc. However, the operating steps of these methods are cumbersome and complicated, and they need to be carried out in the laboratory with certain equipment, instruments, utensils and chemical reagents. Whether in terms of operation and maintenance, cost or accuracy, they cannot meet the technical requirements for water alkalinity determination.
[0004] Weakly acidic resin can react with alkaline substances in water, thereby changing the conductivity of water, and the alkalinity of water can be detected by the change in conductivity. However, the weakly acidic resin prepared in the prior art contains a lot of unreacted polymerized monomers. When the weakly acidic resin containing a lot of unreacted polymerized monomers is used for water sample alkalinity testing, the monomers are easily dissolved, affecting the accuracy of water sample alkalinity testing; and the prepared weakly acidic resin has a low carboxyl content, and the water sample alkalinity testing efficiency is low. Summary of the invention
[0005] In view of the deficiencies in the prior art, the present invention provides a weak acid substrate with low dissolution in a water sample. The structure of the weak acid substrate contains a hyperbranched unsaturated polymer, and a double bond- and carboxyl-containing monomer is grafted into the side chain of the hyperbranched unsaturated polymer, so that the prepared weak acid substrate contains a large number of carboxyl groups. When the weak acid substrate is used for water sample detection, the reaction rate of the weak acid substrate and alkaline substances can be increased, and the accuracy of alkalinity detection can be improved. When preparing the weak acid substrate, the excess double bond- and carboxyl-containing monomer that has not reacted is washed away and then a cross-linking reaction is performed, so as to reduce the presence of the residual double bond- and carboxyl-containing monomer in the system, reduce the dissolution rate of the weak acid substrate in the water sample, and further improve the accuracy of alkalinity detection.
[0006] The invention aims to provide a weak acid substrate with low solubility in water samples. The weak acid substrate is prepared by polymerizing a hyperbranched unsaturated resin and a monomer containing a double bond and a carboxyl group at a mass ratio of 1:80-100 under the action of an initiator, and then crosslinking and curing.
[0007] Preferably, the hyperbranched unsaturated resin is selected from one or more of an unsaturated hyperbranched polyurethane prepolymer, an unsaturated hyperbranched polyacrylate prepolymer, an unsaturated hyperbranched silicone prepolymer and an unsaturated hyperbranched polyester prepolymer; the unsaturated double bonds in the hyperbranched unsaturated resin selected in this embodiment are highly reactive, and monomers containing double bonds and carboxyl groups can be grafted into the side chains to introduce more carboxyl groups into the polymer.
[0008] Preferably, the monomer containing double bonds and carboxyl groups is selected from one or more of methacrylic acid, 2-(trifluoromethyl)acrylic acid, cinnamic acid, acrylic acid, maleic acid, and itaconic acid; the double bonds of the monomer containing double bonds and carboxyl groups used in this embodiment have high reactivity, and the copolymer molecular chain obtained by polymerization contains more carboxyl active reactive groups.
[0009] Preferably, the initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, tert-butyl benzoyl peroxide, tert-amyl benzoyl peroxide and tert-butyl peroxy-2-ethylhexanoate.
[0010] Another object of the present invention is to provide a method for preparing a weak acid substrate with low solubility in water samples, characterized in that it comprises the following steps:
[0011] S1. The initiator is dissolved in a solvent, and the temperature is slowly raised, a hyperbranched unsaturated resin is added with stirring, a double bond and a carboxyl monomer is added dropwise, the reaction is stirred, and post-processed to obtain a copolymer;
[0012] S2. The copolymer prepared in step S1 is mixed with a cross-linking agent, and the mixture is thermally cross-linked to obtain a weak acid substrate with low solubility in water samples.
[0013] Furthermore, in step S1, the solvent is selected from one or more of toluene, ethyl acetate, xylene, tetrahydrofuran, dimethylformamide, dimethyl carbonate, diphenyl carbonate, cyclohexanone, ethylene glycol monomethyl ether, toluene cyclohexanone, ethylene glycol monoethyl ether, isopentyl 2-methylbutyrate and 3-ethyl ether ethyl propionate; the selection of the solvent is mainly to reduce the concentration of free radical polymerization and slow down the reaction exotherm so as to better control the structure of the polymer.
[0014] Furthermore, in step S1, the amount of the initiator used is 1-5% of the mass of the monomer containing double bonds and carboxyl groups.
[0015] Furthermore, in step S1, the heating temperature is 50-110°C; the heating temperature is selected based on the decomposition temperature of the initiator.
[0016] Furthermore, in step S1, the reaction time is 1-3 hours.
[0017] Furthermore, in step S1, the post-treatment is continuous washing with water / ethanol; the continuous washing with water / ethanol is to wash away the remaining double bond and carboxyl monomers that have not reacted, reduce the presence of remaining double bond and carboxyl monomers in the system, reduce the dissolution rate of the weak acid substrate in the water sample, and improve the accuracy of alkalinity detection.
[0018] Furthermore, in step S2, the cross-linking agent is one or both of dicumyl peroxide and benzoyl peroxide; the cross-linking agent selected in this scheme can be decomposed by heat to generate free radicals, which can be cross-linked by heating with the polymer.
[0019] Furthermore, in step S2, the cross-linking agent is 20-40% of the mass of the copolymer obtained in step S1.
[0020] Furthermore, in step S2, the heating temperature is 100-110°C; the heating temperature is selected based on the decomposition temperature of the initiator.
[0021] Furthermore, in step S2, the reaction time is 0.5-2 hours.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] (1) The present invention synthesizes a weak acid substrate with low solubility in water samples. The structure of the weak acid substrate contains a hyperbranched unsaturated polymer, and a double bond and a carboxyl monomer are grafted into the side chain of the hyperbranched unsaturated polymer, so that the prepared weak acid substrate contains a large number of carboxyl groups. When the weak acid substrate is used in water sample detection, the reaction rate between the weak acid substrate and the alkaline substance can be increased, thereby improving the accuracy of alkalinity detection.
[0024] (2) In the process of preparing the weak acid substrate of the present invention, the hyperbranched unsaturated polymer and the monomer containing double bonds and carboxyl groups are first polymerized, and the unreacted monomers are washed away and then cross-linked and cured, thereby reducing the presence of residual monomers in the system, reducing the dissolution rate of the weak acid substrate in the water sample, and improving the accuracy of alkalinity detection. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 A linear relationship fitting diagram was constructed for the weakly acidic substrate prepared in Example 1 regarding the correlation between the conductivity change value of the water sample and the alkalinity value.
[0026] Figure 2 A linear relationship fitting diagram was constructed for the weakly acidic substrate prepared in Example 2 regarding the correlation between the conductivity change value of the water sample and the alkalinity value.
[0027] Figure 3 A linear relationship fitting diagram was constructed for the weakly acidic substrate prepared in Example 3 regarding the correlation between the conductivity change value of the water sample and the alkalinity value.
[0028] Figure 4 Construct a linear relationship fitting diagram for Rohm and Haas Amberlite IRC76 regarding the correlation between the change in conductivity of water samples and the alkalinity value. DETAILED DESCRIPTION
[0029] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention and the accompanying drawings. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0030] Example 1
[0031] S1. Azobisisobutyronitrile (0.8 g) was dissolved in 20 mL of ethyl acetate and the temperature was slowly raised to 55°C. Unsaturated hyperbranched polyacrylate prepolymer (1 g) was added and stirred. 2-(trifluoromethyl)acrylic acid (80 g) was added dropwise. The mixture was stirred for 1 hour and washed with water / ethanol to obtain a copolymer.
[0032] S2. The copolymer (20 g) obtained in step S1 and benzoyl peroxide (4 g) were mixed, and the mixture was co-heat-crosslinked at 100° C. for 0.5 hours to obtain a weak acid substrate with low solubility in water samples.
[0033] Example 2
[0034] S1. Dissolve benzoyl peroxide (5 g) in 20 mL toluene and slowly heat to 110°C, add unsaturated hyperbranched silicone prepolymer (1 g) and stir, add acrylic acid (100 g) dropwise, stir and react for 2 hours, wash with water / ethanol continuously to obtain a copolymer;
[0035] S2. The copolymer (20 g) obtained in step S1 and diisopropylbenzene peroxide (8 g) were mixed, and the mixture was co-heat-crosslinked at 110° C. for 1 hour to obtain a weak acid substrate with low solubility in water samples.
[0036] Example 3
[0037] S1. Dissolve tert-butyl benzoyl peroxide (2.7 g) in 20 mL of xylene and slowly heat to 70°C, add unsaturated hyperbranched polyester prepolymer (1 g) and stir, add methacrylic acid (90 g) dropwise, stir and react for 2 hours, wash with water / ethanol continuously to obtain a copolymer;
[0038] S2. The copolymer (20 g) obtained in step S1 and benzoyl peroxide (6 g) were mixed, and the mixture was co-heat-crosslinked at 100° C. for 2 hours to obtain a weak acid substrate with low solubility in water samples.
[0039] Performance Test:
[0040] The weak acid substrate with low solubility in water samples and Rohm and Haas Amberlite IRC76 prepared in Examples 1-3 involved are subjected to the following pretreatment before use: a certain mass of the weak acid substrate with low solubility in water samples and Rohm and Haas Amberlite IRC76 prepared in Examples 1-3 are weighed and soaked in deionized water respectively to remove the dissolved substances in the weak acid substrate with low solubility in water samples and Rohm and Haas Amberlite IRC76 prepared in Examples 1-3, respectively. The soaking is continued with constant stirring. After about 12 hours, the weak acid substrate with low solubility in water samples and Rohm and Haas Amberlite IRC76 prepared in Examples 1-3 are respectively fished out, and the acidic resin is washed with a large amount of deionized water and dried for later use.
[0041] The weakly acidic substrates with low solubility in the water samples prepared in Examples 1-3 were respectively soaked in pure water and tap water for 24 hours, and the changes in conductivity were observed. The test results are shown in Table 1.
[0042] Table 1. Test results of the changes in conductivity of water samples by the resin materials prepared in Examples 1-3.
[0043] Example Changes in conductivity of pure water Changes in conductivity of soaked tap water Example 1 <10% 35.5% Example 2 <10% 36.9% Example 3 <10% 40.7%
[0044] It can be seen from Table 1 that when the weak acid substrate with low solubility in the water samples prepared in Examples 1-3 of the present invention is soaked in pure water, the conductivity of the pure water changes by less than 10%, indicating that the weak acid substrate with low solubility in the water samples prepared in Examples 1-3 of the present invention hardly contributes to the conductivity of the water body. When the weak acid substrate with low solubility in the water samples prepared in Examples 1-3 of the present invention is soaked in tap water, the conductivity of the tap water changes significantly, indicating that the weak acid substrate with low solubility in the water samples prepared in Examples 1-3 of the present invention can fully react with the water sample to significantly change the conductivity of the water sample, and is suitable for detecting the alkalinity of the water sample.
[0045] Water sample alkalinity test:
[0046] S1. Using water samples with gradient alkalinity values (as shown in Table 2) as gradient standards, the conductivity of each gradient standard is measured respectively;
[0047] S2. Each gradient standard was mixed with a weak acid substrate or a commercially available acid resin (Rohm and Haas Amberlite IRC76) having low solubility in the water sample prepared in Examples 1-3;
[0048] S3. Test the conductivity value of each gradient standard;
[0049] S4. For the same standard product, the conductivity value measured for the first time is T1, and the conductivity value measured for the second time is T2. The conductivity change values (i.e., T1-T2) of each gradient standard product before and after the reaction with the low-soluble weak acid substrate or commercially available acid resin in the water sample prepared in Examples 1-3 are sorted out. The mass of water used for this test is 80 g, the low-soluble weak acid substrate in the water sample prepared in Examples 1-3 is drained is 10 g, and the drained Rohm and Haas Amberlite IRC76 is 20 g. The conductivity change value is the horizontal coordinate, and the alkalinity value of the water sample is the vertical coordinate. A linear relationship curve is fitted, as shown in FIG. Figure 1 , Figure 2 , Figure 3 , Figure 4 shown.
[0050] Table 2. Data involved in constructing a linear relationship for a weak acid substrate with low solubility in water samples prepared in Example 4.
[0051] Standards Initial alkalinity (mg / L) T1 / μs T1-T2 / μs Theoretical conductivity drop value / μs Relative error A tap water 42 116.7 35.4 33.2 6.6% B tap water 125 476.8 181.5 184.2 1.5% C tap water 97 324.1 140.1 133.3 5.1% D tap water 204 701.5 316.6 327.9 3.4% E place tap water 158 598.5 231.7 244.2 5.1% F tap water 172 646.3 272.2 269.7 0.9% G tap water 276 823.8 475.3 458.8 3.6% H tap water 71 219.4 93.3 86.0 8.5% I local tap water 231 956.2 367.9 377.0 2.4%
[0052] From Table 2 and Figure 1 It can be found that when the weak acid substrate with low solubility in the water sample prepared in Example 4 is used to detect the alkalinity of the water sample, the change value of the water sample conductivity has a strong linear relationship with the alkalinity of the water sample, indicating that the weak acid substrate with low solubility in the water sample prepared in Example 4 of the present invention can be used for testing the alkalinity of the water sample, and when used for testing the alkalinity of the water sample, the relative error is below 8.5%.
[0053] Table 3. Data involved in constructing a linear relationship for a weak acid substrate with low solubility in water samples prepared in Example 5.
[0054]
[0055]
[0056] From Table 3 and Figure 2 It can be found that when the weak acid substrate with low solubility in the water sample prepared in Example 5 is used to detect the alkalinity of the water sample, the change value of the water sample conductivity has a strong linear relationship with the alkalinity of the water sample, indicating that the weak acid substrate with low solubility in the water sample prepared in Example 5 of the present invention can be used for testing the alkalinity of the water sample, and the relative error is less than 8.3%.
[0057] Table 4. Data involved in constructing a linear relationship for a weak acid substrate with low solubility in water samples prepared in Example 6.
[0058] Standards Initial alkalinity (mg / L) T1 / μs T1-T2 / μs Theoretical conductivity drop value / μs Relative error A tap water 42 116.7 33.7 31.9 5.6% B tap water 125 476.8 179.8 182.0 1.2% C tap water 97 324.1 139.7 131.3 6.4% D tap water 204 701.5 314.2 324.8 3.3% E place tap water 158 598.5 228.4 241.6 5.5% F tap water 172 646.3 270.2 266.9 1.2% G tap water 276 823.8 471.1 454.9 3.6% H tap water 71 219.4 90.5 84.3 7.3% I local tap water 231 956.2 363.8 373.6 2.6%
[0059] From Table 4 and Figure 3It can be found that when the weak acid substrate with low solubility in the water sample prepared in Example 6 is used to detect the alkalinity of the water sample, the change value of the water sample conductivity has a strong linear relationship with the alkalinity of the water sample, indicating that the weak acid substrate with low solubility in the water sample prepared in Example 6 of the present invention can be used for testing the alkalinity of the water sample, and the relative error is less than 7.3%.
[0060] Table 5. Data involved in constructing the linear relationship for Rohm and Haas Amberlite IRC76.
[0061]
[0062]
[0063] From Table 5 and Figure 4 It can be found that when Rohm and Haas Amberlite IRC76 is used to detect the alkalinity of water samples, the linear relationship between the change in conductivity of the water samples and the alkalinity of the water samples is weak, indicating that the error of Rohm and Haas Amberlite IRC76 when used to test the alkalinity of water samples is large, and the relative error can reach 32.4%.
[0064] In summary, when the weak acid substrate with low solubility in water samples prepared in Examples 1-3 of the present invention is used for water sample alkalinity testing, the relative error is smaller than that of conventional weak acid resins (such as Rohm and Haas Amberlite IRC76).
[0065] Water sample alkalinity test:
[0066] The weak acid substrate with low dissolution in the water sample prepared by Examples 1-3 of the present invention and Rohm and Haas Amberlite IRC76 and the attached Figure 1-4 The linear relationship shown in the figure is used to test the alkalinity of the water sample. The specific operation is as follows:
[0067] S1. Before testing the water sample, the conductivity of the test water is measured with a conductivity meter and recorded as C1. Then, the low-soluble weak acid substrate and Rohm and Haas Amberlite IRC76 in the water samples prepared in Examples 1-3 are respectively mixed with the test water and stirred for about 2 hours. The mass of the test water is 80 g, the low-soluble weak acid substrate in the water samples prepared in Examples 1-3 is drained is 10 g, and the drained Rohm and Haas Amberlite IRC76 is 20 g. The conductivity of the water after stirring for 2 hours is measured and recorded as C2.
[0068] S2. Calculate the conductivity change values (i.e., C1-C2) of the water sample before and after the reaction with the low-dissolving weak acid substrate and Rohm and Haas Amberlite IRC76 in the water sample prepared in Examples 1-3, and bring the conductivity change values calculated into the attached Figure 1-4The linear relationship is shown in Table 6.
[0069] Table 6. Application attachment Figure 1-4 The linear relationship shown is used to estimate the alkalinity value of the water sample.
[0070]
[0071]
[0072] It can be seen from Table 6 that when the weak acid substrates prepared in Examples 1-3 of the present invention are used for water sample alkalinity testing, the relative errors of the measured water sample alkalinity are all less than 10%, while when commercially available acidic resins (such as Rohm and Haas Amberlite IRC76) are used for water sample alkalinity testing, the relative errors of the measured water sample alkalinity are all greater than 10%.
[0073] In summary, when the weak acid substrates prepared in Examples 1-3 of the present invention are used for water sample alkalinity testing, the relative error is small and the accuracy is high compared to commercially available acidic resins (such as Rohm and Haas Amberlite IRC76).
[0074] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that after reading the specification of this application, the technicians can still modify or replace the specific implementation mode of the present invention with equivalents, but these modifications or changes do not deviate from the scope of protection of the pending claims of the present application.
Claims
1. A weak acid substrate with low solubility in water samples, characterized in that The weak acid substrate is prepared by polymerizing a hyperbranched unsaturated resin and a monomer containing a double bond and a carboxyl group at a mass ratio of 1:80-100 under the action of an initiator, and then crosslinking and curing; The method for preparing the weak acid substrate with low solubility in water sample comprises the following steps: S1. The initiator is dissolved in a solvent, and the temperature is slowly raised, a hyperbranched unsaturated resin is added with stirring, a double bond and a carboxyl monomer is added dropwise, the reaction is stirred, and post-processed to obtain a copolymer; S2. mixing the copolymer obtained in step S1 and the crosslinking agent, and co-heat crosslinking to obtain a weak acid substrate with low solubility in water samples; In step S1, the post-treatment is continuous washing with water / ethanol.
2. The weakly acidic substrate with low solubility in water sample according to claim 1, characterized in that: The hyperbranched unsaturated resin is selected from one or more of an unsaturated hyperbranched polyurethane prepolymer, an unsaturated hyperbranched polyacrylate prepolymer, an unsaturated hyperbranched silicone prepolymer and an unsaturated hyperbranched polyester prepolymer.
3. The weakly acidic substrate with low solubility in water sample according to claim 2, characterized in that: The double bond and carboxyl monomer is selected from one or more of methacrylic acid, 2-(trifluoromethyl)acrylic acid, cinnamic acid, acrylic acid, maleic acid, and itaconic acid.
4. The weakly acidic substrate with low solubility in water sample according to claim 1, characterized in that: The initiator is selected from one or more of azobisisobutyronitrile, azobisisoheptanenitrile, benzoyl peroxide, tert-butyl benzoyl peroxide, tert-amyl benzoyl peroxide and tert-butyl peroxy-2-ethylhexanoate.
5. The weak acid substrate with low solubility in water sample according to claim 1, characterized in that In step S1, the solvent is selected from one or more of toluene, ethyl acetate, xylene, tetrahydrofuran, dimethylformamide, dimethyl carbonate, diphenyl carbonate, cyclohexanone, ethylene glycol monomethyl ether, toluene cyclohexanone, ethylene glycol monoethyl ether, isopentyl 2-methylbutyrate and 3-ethyl ethyl propionate.
6. The weakly acidic substrate with low solubility in water sample according to claim 1, characterized in that: In step S1, the amount of the initiator used is 1-5% of the mass of the monomer containing double bonds and carboxyl groups.
7. The weakly acidic substrate with low solubility in water sample according to claim 1, characterized in that: In step S1, slowly raise the temperature to 50-110 o C.
8. The weakly acidic substrate with low solubility in water sample according to claim 1, characterized in that: In step S2, the cross-linking agent is one or both of dicumyl peroxide and benzoyl peroxide.
9. The weakly acidic substrate with low solubility in water sample according to claim 1, characterized in that: In step S2, the cross-linking agent is 20-40% of the mass of the copolymer obtained in step S1.
Citation Information
Patent Citations
Preparation method of hyperbranched viscosity reduction type polycarboxylate water reducer
CN111704698A
Water absorbent resin particles of crosslinked carboxyl-containing polymeres with low monomer content
CN1484654A
